El storytelling como estrategia de posicionamiento de mercado para la Agencia de Diseño Studio Reel en la ciudad de Ambato - Verdesoto Acosta, Kevin Paúl (2023)
Storytelling is a communication technique that helps companies create links with the user contributing to a better positioning within the market. For this reason the The objective of this research was to propose storytelling as a marketing strategy positioning for the Studio Reel Design Agency in the city of Ambato. for which The descriptive, correlational cross-sectional level was applied as methodology: because sought the description of the factors and elements involved in the development of storytelling for the study agency. The study population were companies that receive services from the agency. The main findings focus on a weak positioning of the company, and poor content promotion about the brand and its processes. Regarding storytelling evidenced ignorance of the benefits of this technique so its use is scarce as a communication tool. In correspondence with the expert criteria determined the need to design a proposal that responds to the communicational and marketing needs of the company in order to open new horizons that contribute to the improvement of its image. This proposal is will be characterized by the use of attractive audiovisual content, established under a optimal time and format to capture the attention of users in social networks of trend.